2014
DOI: 10.1038/npp.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pharmacological Modulation of the Steroid Sulfatase Axis Improves Response Control; Comparison with Drugs Used in ADHD

Abstract: Maladaptive response control is a feature of many neuropsychiatric conditions, including attention deficit hyperactivity disorder (ADHD). As ADHD is more commonly diagnosed in males than females, a pathogenic role for sex-linked genes has been suggested. Deletion or point mutation of the X-linked STS gene, encoding the enzyme steroid sulfatase (STS) influences risk for ADHD. We examined whether deletion of the Sts gene in the 39,X(Y*)O mouse model, or pharmacological manipulation of the STS axis, via administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 56 publications
4
27
1
Order By: Relevance
“…2a, main effect of GENOTYPE, F 1,27 = 0.58, P = 0.45). The lack of differences in impulsive behaviour in this task was further demonstrated by another measure of response inhibition, the speed of stopping or SSRT derived, as is conventional (Bari et al 2009;Davies et al 2014;Humby et al 2013), in sessions where the subjects exhibited 50% correct stopping. Equivalent SSRTs were observed in both Nesp m/+ and control mice ( Fig.…”
Section: Nesp M/+ Mice Show No Differences In Impulsive Responding Inmentioning
confidence: 81%
“…2a, main effect of GENOTYPE, F 1,27 = 0.58, P = 0.45). The lack of differences in impulsive behaviour in this task was further demonstrated by another measure of response inhibition, the speed of stopping or SSRT derived, as is conventional (Bari et al 2009;Davies et al 2014;Humby et al 2013), in sessions where the subjects exhibited 50% correct stopping. Equivalent SSRTs were observed in both Nesp m/+ and control mice ( Fig.…”
Section: Nesp M/+ Mice Show No Differences In Impulsive Responding Inmentioning
confidence: 81%
“…Nevertheless, dysregulation of Sts in 40, XXY mice may still occur (e.g., due to skewed X-inactivation – X vs. X Y* – and/or escape from inactivation). Interest in STS as a contributor to phenotypic features of KS remains high because of previous studies in mice (Davies et al, 2009, 2014), and because of the association of STS with cognitive function and deficits in humans (Cavenagh et al, 2019; Chatterjee et al, 2016; Kent et al, 2008; Stergiakouli et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A study of female carriers revealed a comparable suite of behavioural differences from control subjects, together with an increased likelihood of postpartum depression 6. The pattern of behavioural phenotypes seen in males with XLI/carrier females overlaps with that seen in STS-deficient mice,13–17 and may therefore be largely ascribed to biological effects of STS deficiency rather than ascertainment or socialisation effects. Previous behavioural phenotyping approaches in XLI have been suboptimal: a) survey-based studies did not collect genetic data and so could not objectively confirm or define STS deletion carrier status, and these studies may theoretically have elicited responses from more severely affected individuals inflating risk estimates, b) only relatively early age points have been assessed (average age <45 years) and c) studies have had either no control group, or no contemporaneously recruited control group.…”
Section: Introductionmentioning
confidence: 89%